Medical image encryption based on DCT-DWT domain combining 2D-DataMatrix Barcode - Nambutdee, Amarit; Airphaiboon, Surapan (My University, 2016)
In this paper, an application for medical image encryption and watermarking to store patient information is proposed. By using scrambling algorithm, the 1st view patient information is hidden and require unique patient password to access a real image. For watermarking scene, a Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) are applied to non-overlapping block size 8x8 image pixels. Later, a DWT and DCT coefficient value are compared in each block for position identification of embed message in medical image. To improve high capacity and imperceptibility in watermarking step, a Two Dimension Barcode ECC200 standard is used to convert message before embed to cover image. Experimental results demonstrate that the proposed scheme achieves better performance of imperceptibility.
Keywords: DCT; Digital Watermarking; DWT; Encryption; Error Correction; Robustness; Scramble; Two-Dimensional Data Matrix Barcode